Hydrogen-sensitive material, water-based paint and preparation method and application thereof
Patent Information
- Application Number
- CN202611452780.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-18
- Publication Date
- 2026-10-27
AI Technical Summary
[0007]为了解决现有氢气检测技术在低温环境下响应速度慢、难以实现大面积连续覆盖、选择性及可逆复用性能不足,并且施工安全性和规模化制备适应性受限的问题,本发明提出了一种氢敏材料、水性喷漆及其制备方法与应用
1.本发明通过调控含钨前驱体系的pH及水热反应条件,分别构建了六方相WO3纳米棒和单斜相WO3纳米颗粒,并通过球磨使Pt活性组分负载于WO3表面,形成兼具气体传输通道和氢气活化能力的氢敏材料。其中,六方相WO3纳米棒相互交错搭接形成连通孔隙,单斜相WO3纳米颗粒分散均匀并形成颗粒间隙,均能够促进氢气和氧气在材料内部的扩散,增加WO3表面与气体的有效接触;Pt活性组分能够促进氢气的吸附和解离,加快活性氢物种与WO3之间的作用,从而提高材料在低温条件下的变色响应速度(在18℃条件下,通入氢气15 s即可出现颜色变化,2 min时接近完全变色)。重新通入空气后,氧气能够沿孔隙或颗粒间隙进入材料内部,促进活性氢物种从WO3晶格中脱除,使材料恢复至初始颜色。本发明提供的氢敏材料能够在氢气变色与空气褪色过程中保持稳定的响应和恢复性能,经多次循环后仍可恢复至初始颜色,且未出现明显颜色残留,从而实现可逆复用,显著延长了氢敏材料的有效使用周期,满足低温环境下氢气泄漏长期可视化监测的需求。
Smart Images

Figure CN122978765A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of hydrogen-sensitive materials technology, specifically to a hydrogen-sensitive material, a water-based spray paint, its preparation method, and its application. Background Technology
[0002] Hydrogen energy is characterized by its cleanliness, high efficiency, and wide range of applications, and has been gradually applied in hydrogen production, storage, transportation, and utilization. However, due to the small size and high permeability of hydrogen molecules, leaks are easily detected from hydrogen storage containers, pipelines, valves, joints, and welds. Furthermore, hydrogen has a wide explosive limit and low ignition energy, posing a risk of combustion and explosion after a leak. Prolonged infiltration of hydrogen into metallic materials can also induce hydrogen embrittlement. Therefore, timely and accurate hydrogen leak detection is crucial for ensuring the safe operation of hydrogen energy equipment.
[0003] Current hydrogen detection typically employs electrochemical or resistive sensors. Electrochemical sensors generate electrical signals through the redox reaction of hydrogen on the electrode surface, offering advantages such as high sensitivity and ease of quantitative detection. However, they usually require power supplies, signal acquisition and transmission devices, and regular calibration and maintenance. At low temperatures, the electrolyte conductivity and electrode reaction rate decrease, potentially slowing the response. These sensors typically only provide point-based detection of hydrogen near the installation location. For large hydrogen storage facilities or long-distance hydrogen pipelines, numerous detection nodes are required, increasing installation and maintenance costs. Resistive hydrogen sensors detect changes in resistance caused by the interaction of hydrogen with a sensitive material. They are relatively simple in structure and low in cost, but their detection signals are easily affected by environmental factors such as methane, carbon monoxide, volatile organic compounds, water vapor, and oil fumes, potentially causing cross-response and affecting the accuracy of the results. Some resistive sensors also require operation at specific temperatures, increasing power supply and temperature control requirements. Because they also primarily provide localized detection, they struggle to achieve continuous and comprehensive leak monitoring in high-altitude, obstructed areas, complex pipelines, and large equipment surfaces.
[0004] To expand the detection range, existing technologies also fabricate hydrogen-sensitive materials into color-changing films, labels, or indicator sheets, and place them at locations prone to leakage, such as valves, flanges, and pipe connections. These materials can directly indicate hydrogen leaks through color changes, without relying on complex detection circuits. However, the fixed size and shape of prefabricated films or labels make it difficult to fully adhere to curved surfaces, irregularly shaped parts, welds, and complex connection areas. When used in large equipment such as hydrogen storage tanks and pipelines, they need to be laid piece by piece, resulting in low construction efficiency and the potential for uncovered areas between adjacent films. Different hydrogen energy equipment has varying substrate types, surface roughness, and thermal expansion properties. Existing films or labels typically rely on adhesive layers or specialized substrates, which are prone to hardening, cracking, peeling, or detachment under long-term low-temperature or thermal cycling conditions, affecting long-term adhesion stability. Simultaneously, low temperatures slow down the diffusion and reaction rate of hydrogen in the film layer, leading to delayed colorimetric response. Some hydrogen-sensitive materials recover slowly after color development, and after repeated use, color residue, activity decay, or a decrease in response speed may occur, affecting reversible reuse performance and service life. In addition, the color development process of some visual hydrogen-sensitive materials is easily affected by ambient temperature, humidity or other reducing gases, causing unstable color changes or non-target responses, which in turn affects the accuracy of hydrogen leak detection.
[0005] Some hydrogen-sensitive materials require dispersion, film formation, or on-site coating using organic solvents. The evaporation of organic solvents increases volatile organic compound (VOC) emissions and places higher demands on ventilation, anti-static, and fire prevention measures at the construction site, especially near flammable and explosive facilities such as hydrogen storage and transportation facilities, increasing the difficulty of on-site safety management. Some hydrogen-sensitive color-changing materials also require multiple steps, including active component loading, material compounding, film formation, and post-treatment, making them highly sensitive to material ratios, film thickness, and film formation conditions. Relying on specialized substrates, precision coating equipment, or stringent processing conditions during preparation can easily increase the difficulty of product consistency control and production costs, hindering continuous production and large-scale application.
[0006] Therefore, how to achieve continuous, large-area coverage of hydrogen energy equipment surfaces without relying on complex power supply and signal transmission devices, while taking into account rapid response at low temperatures, hydrogen selectivity, reversible reuse performance and long-term adhesion stability, and reducing the safety burden and preparation cost of on-site construction, remains a technical problem that urgently needs to be solved in this field. Summary of the Invention
[0007] To address the shortcomings of existing hydrogen detection technologies, such as slow response speed at low temperatures, difficulty in achieving large-area continuous coverage, insufficient selectivity and reversible reusability, and limitations in construction safety and large-scale preparation adaptability, this invention proposes a hydrogen-sensitive material, a water-based spray paint, its preparation method, and its application. The technical solution of this invention is as follows: A method for preparing a hydrogen-sensitive material includes the following preparation steps: The pH of the tungsten precursor system was adjusted and a hydrothermal reaction was carried out. After post-treatment, WO3 nanomaterials were obtained. The WO3 nanomaterials were mixed with a Pt precursor solution, ball-milled, separated, and dried to obtain a hydrogen-sensitive material. The tungsten-containing precursor is Na2WO4·2H2O, H2WO4, WCl6, or (NH4). 10 W 12 O 41 The WO3 precursor is any one of Na2WO4·2H2O; the Pt precursor is any one of chloroplatinic acid, platinum nitrate, and tetraammineplatinum nitrate; the mass of Pt in the Pt precursor solution is 0.5-2% of the mass of the WO3 nanomaterial; when the tungsten-containing precursor is Na2WO4·2H2O, the WO3 nanomaterial is WO3 nanorods, the WO3 nanorods have a hexagonal crystal phase, a diameter of 50-200 nm, and a length of 1-4 μm; when the tungsten-containing precursor is H2WO4, the WO3 nanomaterial is WO3 particles, the WO3 particles have a monoclinic crystal phase.
[0008] Furthermore, the hydrothermal reaction temperature is 160~220℃, and the time is 4~10 h; the post-treatment steps include separation, washing, and drying; the ball milling time is 6~24 h, and the ball milling speed is 300~500 rpm; the drying temperature is 60~100℃, and the time is 12~36 h.
[0009] Further, when the tungsten-containing precursor is Na2WO4·2H2O, the step of adjusting the pH of the tungsten-containing precursor system is as follows: adding an inorganic acid to the Na2WO4·2H2O solution to adjust the pH to 1.5~2.5, diluting with water to adjust the pH to 2.5~3.5, adding an organic acid to adjust the pH to 2.0~3.0, and finally introducing an inorganic salt; the inorganic acid is hydrochloric acid or nitric acid; the organic acid is oxalic acid or citric acid; and the inorganic salt is sodium chloride or potassium chloride.
[0010] Furthermore, when the tungsten-containing precursor is H2WO4, the step of adjusting the pH of the tungsten-containing precursor system is as follows: add an alkaline pH adjuster to the H2WO4 suspension to adjust the pH value to 7.0~8.0; the alkaline pH adjuster is any one of ammonia, ammonium carbonate, and sodium hydroxide.
[0011] A hydrogen-sensitive material is prepared by the above-described preparation method.
[0012] A water-based spray paint, comprising the following components by weight: The film-forming resin comprises 35-45 parts, the hydrogen-sensitive material comprises 15-25 parts, the additives comprises 3-5 parts, and the solvent comprises 35-45 parts; the additives include wetting and dispersing agents, defoamers, leveling agents, and multifunctional additives.
[0013] Further, the film-forming resin is any one or a combination of at least two of waterborne acrylic resin, waterborne polyurethane resin, and waterborne epoxy resin; the wetting and dispersing agent is a waterborne wetting and dispersing agent; the defoamer is a waterborne defoamer; the leveling agent is a waterborne leveling agent; the multifunctional additive is any one or a combination of at least two of 2-amino-2-methyl-1-propanol, dimethylethanolamine, and triethanolamine; and the solvent is a mixed solvent composed of ethanol, butanol, deionized water, and propylene glycol in a mass ratio of 40~50:15~25:25~35:5~10.
[0014] A method for preparing the above-mentioned water-based spray paint includes the following preparation steps: The film-forming resin, dispersant, and defoamer are stirred for the first time; a hydrogen-sensitive material is added and stirred for the second time; a solvent, multifunctional additive, and leveling agent are added and stirred for the third time; and a defoamer is added again and stirred for the fourth time to obtain water-based spray paint.
[0015] Furthermore, all stirring is performed using an electronic stirrer; the first and second stirring times are both 2 hours and the speed is 400 rpm; the third stirring time is 10 hours and the speed is 400 rpm; the fourth stirring time is 1 hour and the speed is 400 rpm.
[0016] One application of the above-mentioned water-based spray paint is in the field of visual monitoring of hydrogen leakage in hydrogen energy equipment.
[0017] Compared with existing technologies, this invention solves the problems of slow response speed, difficulty in achieving large-area continuous coverage, insufficient selectivity and reversible reuse performance, and limited construction safety and adaptability to large-scale preparation of existing hydrogen detection technologies. Specifically, the beneficial effects are as follows: 1. This invention constructs hexagonal WO3 nanorods and monoclinic WO3 nanoparticles by controlling the pH and hydrothermal reaction conditions of the tungsten-containing precursor system. Pt active components are then loaded onto the WO3 surface through ball milling, forming a hydrogen-sensitive material with both gas transport channels and hydrogen activation capabilities. The hexagonal WO3 nanorods interlock to form interconnected pores, while the monoclinic WO3 nanoparticles are uniformly dispersed and form interparticle gaps, both promoting the diffusion of hydrogen and oxygen within the material and increasing the effective contact between the WO3 surface and the gases. The Pt active component promotes hydrogen adsorption and dissociation, accelerating the interaction between active hydrogen species and WO3, thereby improving the color change response speed of the material under low-temperature conditions (at...). At 18°C, a color change occurs after 15 seconds of hydrogen gas introduction, and near-complete color change occurs after 2 minutes. Upon re-introduction of air, oxygen can enter the material through pores or interparticle gaps, promoting the removal of active hydrogen species from the WO3 lattice and restoring the material to its initial color. The hydrogen-sensitive material provided by this invention maintains stable response and recovery performance during hydrogen color change and air decolorization. It can still recover to its initial color after multiple cycles without significant color residue, thus achieving reversible reuse and significantly extending the effective service life of the hydrogen-sensitive material, meeting the need for long-term visual monitoring of hydrogen leakage in low-temperature environments.
[0018] 2. This invention uses waterborne acrylic resin as the film-forming matrix. Through a stepwise dispersion and continuous stirring process, hydrogen-sensitive materials are compounded with additives and mixed solvents to obtain a waterborne spray paint that combines film-forming properties and hydrogen-sensitive response capabilities. The wetting and dispersing agents and mixed solvents improve the wetting and dispersion state of the hydrogen-sensitive materials in the waterborne system, inhibiting powder agglomeration and precipitation. The defoamer and leveling agent reduce bubbles, pinholes, and localized film-forming defects, promoting continuous and uniform film formation. The waterborne acrylic resin provides a stable film structure and substrate adhesion, while retaining channels for hydrogen diffusion to the surface of the hydrogen-sensitive materials, thus ensuring coating integrity, hydrogen-sensitive response, and cycle recovery performance. The waterborne spray paint provided by this invention can form a continuous, smooth, and stably adhered hydrogen-sensitive coating on substrates of different shapes and areas, maintaining a rapid and reversible low-temperature hydrogen-sensitive response. This effectively enables large-area continuous visual monitoring and reversible reuse of hydrogen leaks, extending the effective service life of the coating. Furthermore, the water-based formulation used in this invention effectively reduces the use of organic solvents, lowers the emission of volatile organic compounds and the risk of combustion and explosion during on-site construction, thereby improving the existing hydrogen detection technology's inability to simultaneously achieve large-area coverage, reversible reuse, and safe construction.
[0019] 3. The preparation process of this invention mainly includes hydrothermal reaction, ball milling loading, and conventional mixing and dispersion. The process conditions are easy to control, require no complex equipment, and have good repeatability and adaptability to large-scale preparation. The resulting water-based spray paint can be directly sprayed onto flat, curved, irregularly shaped components, and large-area equipment surfaces, allowing for flexible construction according to the actual monitoring area, reducing sensor placement and wiring installation, and lowering the construction and maintenance costs of the hydrogen leak monitoring system. Simultaneously, the hydrogen-sensitive response system formed by WO3 and the Pt active component can target the adsorption, dissociation, and reversible color change processes of hydrogen, and is less likely to produce the same degree of color response to non-target gases, thereby improving the selectivity of hydrogen detection and reducing the risk of false alarms caused by non-target gases in complex environments. Attached Figure Description
[0020] Figure 1 X-ray diffraction pattern of WO3 nanorods prepared in Example 1; Figure 2 Scanning electron microscope image of the WO3 nanorods prepared in Example 1; Figure 3 X-ray diffraction pattern of WO3 particles prepared in Example 2; Figure 4 Scanning electron microscope image of WO3 particles prepared in Example 2; Figure 5 The X-ray diffraction pattern of WO3 powder prepared in Comparative Example 1; Figure 6 Scanning electron microscope image of WO3 powder prepared for Comparative Example 1. Detailed Implementation
[0021] To make the technical solutions of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. It should be noted that the following embodiments are only used to better understand the technical solutions of the present invention and should not be construed as limiting the present invention.
[0022] Example 1. S1: Dissolve 16.5 g of Na2WO4·2H2O in 50 mL of deionized water until fully dissolved. Then, add 2 mol / L HCl to the Na2WO4·2H2O aqueous solution at a rate of 3.5 mL / min until the pH of the Na2WO4·2H2O aqueous solution is 2.0. Continue to add deionized water to dilute the Na2WO4·2H2O aqueous solution to pH 3.0. Finally, add oxalic acid to adjust the pH to 2.5. Add 3 g of NaCl to the pH-adjusted Na2WO4·2H2O solution, stir well, and transfer to a stainless steel reactor lined with polytetrafluoroethylene. Perform hydrothermal reaction at 180℃ for 4 h. After the reaction, cool to room temperature, centrifuge, collect the solid product, wash the solid product three times each with deionized water and anhydrous ethanol, and vacuum dry at 60℃ for 12 h to obtain WO3 nanorods. 5 g of WO3 nanorods were mixed with 100 mL of chloroplatinic acid aqueous solution with a concentration of 1 g / L and ball-milled at 400 rpm for 10 h to obtain a mixed slurry in which Pt was deposited on the surface of WO3. The mixture was filtered and dried at 60 °C for 24 h to obtain a hydrogen-sensitive material.
[0023] S2: Add 4 g of waterborne acrylic resin, 0.2 g of waterborne wetting and dispersing agent, and 0.05 g of waterborne defoamer to an electric stirrer and stir at 400 rpm for 2 h; add 1.6 g of hydrogen-sensitive material and stir at 400 rpm for 2 h; then add 4 g of mixed solvent, wherein the mass ratio of ethanol, butanol, deionized water, and propylene glycol in the mixed solvent is 45:20:30:5; continue to add 0.05 g of 2-amino-2-methyl-1-propanol and 0.05 g of waterborne leveling agent, stir at 400 rpm for 10 h, then add 0.05 g of waterborne defoamer and stir at 400 rpm for 1 h to obtain waterborne spray paint.
[0024] X-ray diffraction tests were performed on the WO3 nanorods prepared in Example 1, and the test results are as follows: Figure 1 As shown in the figure, the main characteristic diffraction peaks of the WO3 nanorods are consistent with the standard card for hexagonal WO3, and no obvious impurity phase diffraction peaks are observed, indicating that the obtained product is mainly hexagonal WO3. The diffraction peaks are sharp, the background baseline is stable, and no obvious amorphous diffuse peaks are observed, indicating that the obtained WO3 nanorods have good crystallinity and a complete crystal structure. These results demonstrate that the hydrothermal reaction involving NaCl is beneficial to the formation and crystal growth of hexagonal WO3. The stable hexagonal crystal phase provides a good structural basis for the subsequent loading of Pt active components and the hydrogen-sensitive color-changing reaction, and helps the material maintain a rapid hydrogen response at low temperatures.
[0025] like Figure 2 The image shows a scanning electron microscope (SEM) image of the WO3 nanorods prepared in Example 1. As can be seen from the image, the WO3 exhibits a distinct nanorod structure. The nanorods are mainly distributed in diameter between 50 and 200 nm, with lengths ranging from 1 to 4 μm. The rod outlines are clear, the surfaces are smooth, and the overall structure is uniformly dispersed without obvious agglomeration. The nanorods interlock and overlap, forming a connected porous structure, which helps increase the effective specific surface area of the material, exposes more surface active sites, and provides a good structural basis for the diffusion and transport of hydrogen molecules and the subsequent loading of Pt active components. This contributes to improving the response speed and color-changing efficiency of the hydrogen-sensitive material.
[0026] Example 2. The difference between this embodiment and Example 1 lies in S1. 10 g of H2WO4 was added to 250 mL of deionized water and magnetically stirred for 30 min to form a suspension. 25% ammonia solution was added dropwise to the suspension until the pH reached 7.0. The suspension was then transferred to a polytetrafluoroethylene (PTFE) liner with a 70% filling rate, sealed, and placed in an oven for a hydrothermal reaction at 180°C for 10 h. After the reaction, the mixture was cooled to room temperature, centrifuged, washed three times each with deionized water and anhydrous ethanol, and vacuum-dried at 60°C for 12 h to obtain WO3 particles. 5 g of WO3 nanoparticles were mixed with 100 mL of a 1 g / L chloroplatinic acid aqueous solution and ball-milled at 400 rpm for 10 h to obtain a mixed slurry with Pt deposited on the WO3 surface. This slurry was filtered and dried at 60°C for 24 h to obtain a hydrogen-sensitive material. The remaining preparation steps and conditions were the same as in Example 1, resulting in an aqueous spray paint.
[0027] X-ray diffraction tests were performed on the WO3 particles prepared in Example 2, and the test results are as follows: Figure 3 As shown in the figure, the main characteristic diffraction peaks of the WO3 particles are consistent with the standard card for monoclinic WO3, and no obvious impurity phase diffraction peaks are observed, indicating that the obtained product is mainly monoclinic WO3. The diffraction peaks are sharp, the background baseline is stable, and no obvious amorphous diffuse peaks appear, indicating that the WO3 obtained in this embodiment has good crystallinity and a complete crystal structure. The stable monoclinic crystal framework is beneficial for maintaining the structural stability of the material during hydrogen adsorption, discoloration, and recovery processes, providing a good crystal structure basis for the repetitive response of the hydrogen-sensitive material.
[0028] like Figure 4 The image shows a scanning electron microscope (SEM) image of the WO3 particles prepared in Example 2. As can be seen from the image, the obtained WO3 mainly exhibits a regular blocky nanocrystalline morphology, with grain sizes primarily ranging from 100 to 300 nm. The grain outlines are clear, with distinct edges and corners, a smooth surface, and uniform overall dispersion. The nanocrystals stack together to form interparticle pores, providing transport paths for the contact and diffusion of hydrogen molecules. This also facilitates the loading and dispersion of the Pt active component on the WO3 surface, resulting in a hydrogen-sensitive material with excellent hydrogen response performance and reversible color-changing properties.
[0029] Comparative Example 1. The difference between this comparative example and Example 2 lies in S1: 10 g of H2WO4 was directly placed into an alumina crucible and calcined in a muffle furnace at 700°C for 4 h. After calcination, it was cooled to room temperature and crushed in a mortar to obtain WO3 powder. 5 g of WO3 powder was mixed with 100 mL of a 1 g / L aqueous solution of chloroplatinic acid and ball-milled at 400 rpm for 10 h to obtain a mixed slurry with Pt deposited on the WO3 surface. The slurry was filtered and dried at 60°C for 24 h to obtain a hydrogen-sensitive material. The remaining preparation steps and conditions were the same as in Example 2 to obtain an aqueous spray paint.
[0030] X-ray diffraction tests were performed on the WO3 powder prepared in Comparative Example 1, and the test results are as follows: Figure 5 As shown in the figure, the main characteristic diffraction peaks of the WO3 powder are consistent with the standard card for monoclinic WO3, and no obvious impurity phase diffraction peaks are observed, indicating that the obtained product is mainly monoclinic WO3. All diffraction peaks are clear, and no obvious amorphous dispersed peaks appear, indicating that the obtained WO3 has good crystallinity. This result shows that direct calcination of tungstic acid can form a fully crystalline monoclinic WO3, but the particle dispersion state and the exposure of surface active sites cannot be determined solely based on X-ray diffraction results.
[0031] like Figure 6 The image shows a scanning electron microscope (SEM) image of the WO3 powder prepared in Comparative Example 1. As can be seen from the image, the obtained WO3 consists of spherical or ellipsoidal nanocrystals, with the primary grain size mainly distributed between 100 and 400 nm. The grain outlines are rounded and the surface is dense. Multiple nanocrystals tightly aggregate to form agglomerates with significantly increased size, compressing the effective gaps and open channels between particles. This agglomerated structure easily reduces the effective exposed area of the WO3 surface and increases the difficulty of hydrogen diffusion into the agglomerates and uniform loading of the Pt active component. In contrast, the WO3 nanomaterials prepared by the hydrothermal method in this application have a more dispersed nanostructure and abundant interparticle pores, which is beneficial for hydrogen transport, exposure of active sites, and rapid hydrogen-sensitive color-changing reactions.
[0032] Comparative Example 2. The difference between this comparative example and Example 1 is that no hydrogen-sensitive material is introduced. The remaining preparation steps and conditions are the same as in Example 1, resulting in a water-based spray paint.
[0033] Comparative Example 3. The difference between this comparative example and Example 1 is that chloroplatinic acid aqueous solution is not introduced into the hydrogen-sensitive material. 5 g of WO3 nanorods and 100 mL of deionized water are mixed. The remaining preparation steps and conditions are the same as in Example 1 to obtain water-based spray paint.
[0034] Comparative Example 4. The difference between this comparative example and Example 2 is that no hydrogen-sensitive material is introduced. The remaining preparation steps and conditions are the same as in Example 2, resulting in a water-based spray paint.
[0035] Comparative Example 5. The difference between this comparative example and Example 2 is that chloroplatinic acid aqueous solution is not introduced into the hydrogen-sensitive material. 5 g of WO3 nanorods and 100 mL of deionized water are mixed. The remaining preparation steps and conditions are the same as in Example 2 to obtain water-based spray paint.
[0036] (I) Low-temperature hydrogen-sensitive response and reversible recovery performance testing of hydrogen-sensitive materials: To evaluate the hydrogen-sensitive response performance of the hydrogen-sensitive materials prepared in Examples 1-2 and Comparative Examples 1, 3, and 5 under low-temperature conditions, each group of hydrogen-sensitive materials was placed on the surface of a ceramic sheet and evenly spread to form an area of 0.785 cm². 2 Sample layers with a thickness of 1 mm were prepared; each sample was placed inside a quartz tube. The sample was allowed to stand at 18℃ for 2 hours to ensure its temperature was consistent with the ambient temperature. Then, hydrogen gas was introduced into the quartz tube at a flow rate of 10 sccm and a concentration of 99.9%. Timing was started from the moment hydrogen gas was introduced, and the time it took for each sample to show a visually perceptible color change, the time to reach a stable color change state, and the degree of color change were observed and recorded. After the color change test was completed, the hydrogen gas flow was stopped, and air was introduced again. The fading recovery of each sample and the time required to recover to the initial color were recorded to evaluate the reversible response performance of the hydrogen-sensitive material. One hydrogen-induced color change and one air-induced fading were defined as one response cycle. Ten response cycles were performed continuously at the same hydrogen concentration, gas flow rate, and test temperature. The time for the sample to show a significant color change, the time to reach a stable color change state, and the time to recover to the initial color were recorded in the 1st, 3rd, 5th, and 10th cycles, and the presence of color residue, response decay, or irrecoverable color changes after the cycles were observed.
[0037] The test results are shown in Table 1. As can be seen from the table, the hydrogen-sensitive material prepared in Example 1 showed a significant color change after 15 seconds of hydrogen gas introduction at -18℃, and nearly complete color change after 2 minutes, exhibiting a rapid and significant low-temperature hydrogen-sensitive response. This is because the hexagonal WO3 nanorods in Example 1 are interlocked, forming a connected porous structure that provides an effective channel for the diffusion and transport of hydrogen molecules, and exposes more surface active sites. The Pt active component loaded on the WO3 surface promotes the adsorption and dissociation of hydrogen, allowing the generated active hydrogen species to fully interact with WO3, thereby accelerating the color change process. The hydrogen-sensitive material prepared in Example 2 also exhibited a significant color change at low temperatures. This is because the monoclinic WO3 nanoparticles in Example 2 are uniformly dispersed, and the gaps between the particles provide a transport path for the contact and diffusion of hydrogen molecules, and facilitate the loading and utilization of the Pt active component on the WO3 surface, resulting in a hydrogen-sensitive material with good low-temperature hydrogen response performance. After air was reintroduced, both Examples 1 and 2 gradually faded and returned to their initial color within 10 seconds, indicating that both hydrogen-sensitive materials have good reversible response performance. The interconnected pore structure in Example 1 and the diffusion gaps formed between nanoparticles in Example 2 not only facilitate the entry of hydrogen into the material but also promote sufficient contact between oxygen in the air and the material, facilitating the removal of active hydrogen species from the WO3 lattice and restoring WO3 to its initial state. After 10 hydrogen color-changing-air decolorization cycles, the hydrogen-sensitive materials prepared in Examples 1 and 2 still showed significant color changes and returned to their initial color, with no obvious color residue or irreversible deactivation after the cycles. The color-changing time and recovery time in the 10th cycle showed limited changes compared to the first cycle, with color-changing performance retention rates of 88.2% and 85.7%, respectively, indicating that the hydrogen-sensitive materials of this application have stable reversible response performance and good cycle life under low-temperature conditions.
[0038] Although Comparative Example 1 also used Pt-supported monoclinic WO3, its WO3 powder was composed of multiple nanocrystals tightly aggregated into agglomerates. This restricted open pores and effectively exposed surfaces, increasing resistance to hydrogen diffusion into the agglomerates and oxygen participation in the recovery reaction. Therefore, its color change and fading recovery rates were slower than those of Examples 1 and 2. Furthermore, the response and recovery times of Comparative Example 1 showed an increasing trend during cycling, demonstrating that in addition to the crystal phase structure of WO3, the dispersion state and microporous structure of the material affect gas transport, hydrogen-sensitive response, and reversible recovery performance under low-temperature conditions. Comparative Examples 3 and 5 did not introduce the Pt active component, and their hydrogen adsorption and dissociation processes were limited, failing to exhibit hydrogen-sensitive color-changing characteristics. These results indicate that the dispersion state and pore structure of the WO3 nanomaterials, as well as the introduction of the Pt active component, collectively affect the low-temperature response rate and cycling stability of the hydrogen-sensitive material. The above results indicate that by controlling the crystal phase, nanostructure and dispersion state of WO3 and introducing Pt active components on the surface of WO3, the resulting hydrogen-sensitive material exhibits both rapid hydrogen response and good reversible recovery performance under low-temperature conditions.
[0039] Table 1
[0040] (II) Low-temperature hydrogen sensitivity response and reversible recovery performance test of water-based spray paint: To evaluate the hydrogen-sensitive response performance of the water-based spray paints prepared in Examples 1-2 and Comparative Examples 1-5 under low-temperature conditions, each group of water-based spray paints was uniformly sprayed onto the surface of ceramic discs, with the spraying area of each sample controlled to be 3.14 cm². 2 A 2 μm thick dry film was dried at room temperature for 2 h to obtain coated samples. Each sample was placed in a quartz tube and allowed to stand at -18 ℃ for 2 h to ensure the sample temperature matched the ambient temperature. Subsequently, hydrogen gas of a predetermined concentration was introduced into the quartz tube at the same flow rate. Timing was started from the introduction of hydrogen gas, and the time it took for each sample to show a visually perceptible color change, the time to reach a stable color change state, and the degree of color change were observed and recorded. After the color change test was completed, the hydrogen gas was stopped and air was introduced. The time required for each sample to gradually fade and return to its initial color was recorded.
[0041] Based on the above tests, cyclic response tests were conducted. Hydrogen gas was introduced into the sample until a stable color change was achieved. Then, the hydrogen supply was stopped and air was introduced until the sample returned to its initial color. One hydrogen-induced color change and one air-induced color fading were defined as one response cycle. Ten response cycles were continuously performed under the same test temperature, hydrogen concentration, and gas flow rate. The time for the sample to show obvious color change, reach a stable color change, and return to its initial color was recorded in the 1st, 3rd, 5th, and 10th cycles. The presence of color residue, decreased response speed, or incomplete recovery after the cycles was observed. Table 2 below shows the test results for the first and 10th cycles of each embodiment and comparative example. As can be seen from the table, the water-based spray paints prepared in Examples 1 and 2 both exhibited obvious color change after hydrogen introduction and returned to their initial color after air introduction, maintaining good reversible color change capability even after 10 response cycles. In Example 1, the first color change occurred in 60 seconds, and the color change occurred in 70 seconds after the 10th cycle; in Example 2, the corresponding times were 80 seconds and 90 seconds, respectively, indicating that the water-based spray paint prepared in this application still has a fast hydrogen response speed and good cycle stability after the resin film is formed.
[0042] Compared to Example 2, the color change response and color recovery time of Comparative Example 1, prepared using the direct calcination method for WO3 powder, were significantly prolonged. This is mainly because the WO3 nanorods or nanoparticles prepared by the hydrothermal method have better dispersibility and more abundant interparticle pores, which facilitates the rapid diffusion of hydrogen within the coating and its full contact with the active sites. Simultaneously, it promotes the uniform loading of the Pt active component on the WO3 surface, thereby accelerating the catalytic dissociation of hydrogen and the subsequent color change reaction. In Example 1, the WO3 nanorods interlock to form interconnected pores, resulting in a faster hydrogen response and color recovery rate than in Example 2, further demonstrating that the nanorod structure is beneficial for hydrogen transport and the rapid progress of the reversible color change reaction. Comparative Examples 2-5 did not exhibit significant color change under the test conditions, indicating that hydrogen-sensitive materials and their key active components are essential for the hydrogen-sensitive color change response of water-based spray paints. In comparison, neither Comparative Examples 2 nor 4, which did not introduce hydrogen-sensitive materials, showed any color change, indicating that the water-based resin and other coating additives themselves do not possess hydrogen-responsive capabilities. Comparative Example 3, which did not introduce chloroplatinic acid aqueous solution into the hydrogen-sensitive material, also did not show any color change, demonstrating that the Pt active component loaded on the WO3 surface plays a crucial role in the catalytic dissociation of hydrogen and the subsequent reversible color-changing reaction. These comparative results further demonstrate that this application synergistically constructs an effective hydrogen-sensitive response system through WO3 with a specific crystal phase and nanostructure and the Pt active component. Furthermore, after introducing the hydrogen-sensitive material into the water-based spray paint system, it effectively retains the hydrogen-sensitive color-changing performance and recyclability.
[0043] Table 2
[0044] In summary, this invention constructs hexagonal WO3 nanorods and monoclinic WO3 nanoparticles by controlling the pH and hydrothermal reaction conditions of the tungsten-containing precursor system. Pt active components are then loaded onto the WO3 surface through ball milling, forming a hydrogen-sensitive material with both gas transport channels and hydrogen activation capabilities. This achieves reversible reuse of the hydrogen-sensitive material, extending its effective service life and meeting the need for long-term visual monitoring of hydrogen leaks in low-temperature environments. Using waterborne acrylic resin as the film-forming matrix, this invention employs a stepwise dispersion and continuous stirring process to compound the hydrogen-sensitive material with additives and mixed solvents, producing a waterborne spray paint with both film-forming properties and hydrogen-sensitive response capabilities. This enables large-area continuous visual monitoring and reversible reuse of hydrogen leaks, extending the effective service life of the coating. The process conditions of this invention are easy to control, require no complex equipment, and exhibit good repeatability and adaptability for large-scale preparation. Furthermore, it does not readily produce the same degree of color response to non-target gases, thereby improving the selectivity of hydrogen detection and reducing the risk of false alarms caused by non-target gases in complex environments.
[0045] The above description of the embodiments is only for the purpose of helping to understand the method and core ideas of the present invention. It should be noted that those skilled in the art can make several improvements and modifications to the present invention without departing from the principles of the present invention, and these improvements and modifications also fall within the protection scope of the claims of the present invention.
[0046] The above description of the disclosed embodiments enables those skilled in the art to make or use the invention. Various modifications to these embodiments will be readily apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the invention. Therefore, the invention is not to be limited to the embodiments shown herein, but is to be accorded the widest scope consistent with the principles and novel features disclosed herein.
Claims
1. A method for preparing a hydrogen-sensitive material, characterized in that, The preparation steps include the following: The pH of the tungsten precursor system was adjusted and a hydrothermal reaction was carried out. After post-treatment, WO3 nanomaterials were obtained. The WO3 nanomaterials were mixed with a Pt precursor solution, ball-milled, separated, and dried to obtain a hydrogen-sensitive material. The tungsten-containing precursor is Na2WO4·2H2O, H2WO4, WCl6, or (NH4). 10 W 12 O 41 The WO3 precursor is any one of Na2WO4·2H2O; the Pt precursor is any one of chloroplatinic acid, platinum nitrate, and tetraammineplatinum nitrate; the mass of Pt in the Pt precursor solution is 0.5-2% of the mass of the WO3 nanomaterial; when the tungsten-containing precursor is Na2WO4·2H2O, the WO3 nanomaterial is WO3 nanorods, the WO3 nanorods have a hexagonal crystal phase, a diameter of 50-200 nm, and a length of 1-4 μm; when the tungsten-containing precursor is H2WO4, the WO3 nanomaterial is WO3 particles, the WO3 particles have a monoclinic crystal phase.
2. The method for preparing the hydrogen-sensitive material according to claim 1, characterized in that, The hydrothermal reaction is carried out at a temperature of 160~220℃ for 4~10 h; the ball milling time is 6~24 h and the ball milling speed is 300~500 rpm; the drying temperature is 60~100℃ and the drying time is 12~36 h.
3. The method for preparing the hydrogen-sensitive material according to claim 2, characterized in that, When the tungsten-containing precursor is Na2WO4·2H2O, the steps for adjusting the pH of the tungsten-containing precursor system are as follows: add an inorganic acid to the Na2WO4·2H2O solution to adjust the pH to 1.5~2.5, dilute with water to adjust the pH to 2.5~3.5, add an organic acid to adjust the pH to 2.0~3.0, and finally introduce an inorganic salt; the inorganic acid is hydrochloric acid or nitric acid; the organic acid is oxalic acid or citric acid; and the inorganic salt is sodium chloride or potassium chloride.
4. The method for preparing the hydrogen-sensitive material according to claim 2, characterized in that, When the tungsten-containing precursor is H2WO4, the step of adjusting the pH of the tungsten-containing precursor system is as follows: add an alkaline pH adjuster to the H2WO4 suspension to adjust the pH value to 7.0~8.0; the alkaline pH adjuster is any one of ammonia, ammonium carbonate, and sodium hydroxide.
5. A hydrogen-sensitive material, characterized in that, It is prepared by the preparation method according to any one of claims 1-4.
6. A water-based spray paint, characterized in that, By mass, it includes the following components: The film-forming resin comprises 35-45 parts, the hydrogen-sensitive material comprises 15-25 parts, the additives comprises 3-5 parts, and the solvent comprises 35-45 parts; the additives include wetting and dispersing agents, defoamers, leveling agents, and multifunctional additives.
7. The water-based spray paint according to claim 6, characterized in that, The film-forming resin is any one or a combination of at least two of waterborne acrylic resin, waterborne polyurethane resin, and waterborne epoxy resin; the wetting and dispersing agent is a waterborne wetting and dispersing agent; the defoamer is a waterborne defoamer; the leveling agent is a waterborne leveling agent; the multifunctional additive is any one or a combination of at least two of 2-amino-2-methyl-1-propanol, dimethylethanolamine, and triethanolamine; and the solvent is a mixed solvent composed of ethanol, butanol, deionized water, and propylene glycol in a mass ratio of 40~50:15~25:25~35:5~10.
8. A method for preparing a water-based spray paint as described in claim 6 or 7, characterized in that, The preparation steps include the following: The film-forming resin, dispersant, and defoamer are stirred for the first time; a hydrogen-sensitive material is added and stirred for the second time; a solvent, multifunctional additive, and leveling agent are added and stirred for the third time; and a defoamer is added again and stirred for the fourth time to obtain water-based spray paint.
9. The method for preparing water-based spray paint according to claim 8, characterized in that, All stirring was performed using an electronic stirrer; the first and second stirring sessions were each 2 hours long and the stirring speed was 400 rpm; the third stirring session was 10 hours long and the stirring speed was 400 rpm; the fourth stirring session was 1 hour long and the stirring speed was 400 rpm.
10. An application of a water-based spray paint as described in claim 6 or 7, or a water-based spray paint prepared by the preparation method as described in claim 8 or 9, characterized in that, It is applied to the field of visual monitoring of hydrogen leaks in hydrogen energy equipment.